Konsentratga aylangan olma xomashyosidan sharbat ishlab chiqarish jarayonining tuzilmaviy modeli - Abdixalilov, O.U (SCIENCE and SOCIETY, 2023)
The article shows the analysis and experimental work at the fruit production enterprise "Darmon Farm" in Yakkabog District, Kashkadarya Region. One of the most effective methods for producing juice from fruit products is the pressing method. The pressing process in juice production is one of the main ways of obtaining fruit juice in technological industrial conditions, pressing is divided into periodic and continuous pressing. When receiving fruits, the quality of the harvest and the condition size of the fruits are determined juice treatment, temperature processing, filtering, filling, capping, sterilization, labeling, storage.
Keywords: juice products; production; juice straining; temperature change; bottling; sterilization; production technology; labeling; natural substances; chemical reagents; enzymes; juice enrichment; continuous; periodic